Joint features and complementarities of Tspan8 and CD151 revealed in knockdown and knockout models - Yue, Shijing; Zhao, Kun; Erb, Ulrike; Rana, Sanyukta; Zöller, Margot (Biochemical Society transactions, 2017)
Tetraspanins are highly conserved 4-transmembrane proteins which form molecular clusters with a large variety of transmembrane and cytosolic proteins. By these associations tetraspanins are engaged in a multitude of biological processes. Furthermore, tetraspanin complexes are located in specialized microdomains, called tetraspanin-enriched microdomains (TEMs). TEMs provide a signaling platform and are poised for invagination and vesicle formation. These vesicles can be released as exosomes (Exo) and are important in cell contact-independent intercellular communication. Here, we summarize emphasizing knockdown and knockout models' pathophysiological joint and selective activities of CD151 and Tspan8, and discuss the TEM-related engagement of CD151 and Tspan8 in Exo activities.